Correlation of CLEC1B haplotypes with plasma levels of soluble CLEC-2 in healthy individuals. (17th November 2021) - Etemad, Mani; Christodoulou, Foteini; Weiss, Christel; Klüter, Harald; Bugert, Peter
Abstract: Binding of podoplanin to the C-type lectin-like receptor 2 (CLEC-2) promotes platelet activation and soluble CLEC-2 (sCLEC-2) is shed from activated platelets. The role of sCLEC-2 in the plasma is unknown. The expression level and plasma concentration of sCLEC-2 could be affected by variants of the corresponding gene, CLEC1B . Here, we genotyped SNVs in the promoter and coding region of CLEC1B and determined plasma levels of sCLEC-2 in healthy individuals. We genotyped 516 healthy blood donors for 7 SNVs (rs10505743, rs11053538, rs4764178, rs76016091, rs2273986, rs2273987, rs521040) by using PCR methods and calculated haplotypes from the SNV genotypes. For 313 of the donors we measured the sCLEC-2 concentration in EDTA plasma samples by using a commercial ELISA. SNV typing revealed allele frequencies comparable to database information. None of the SNVs showed significant correlation with sCLEC-2 plasma levels. Haplotype analysis indicated 6 haplotypes with frequencies >1% and haplotype h3 was the most frequent (33.8%). Donors homozygous for h3 (n = 37) showed significantly lower sCLEC-2 plasma levels (median 0.95 ng/mL) than donors being h3 negative or heterozygous (n = 276; 1.44 ng/mL; p = .0203). We found that the sCLEC-2 plasma concentration is variable in healthy individuals and the CLEC1B genotype contributes to the expression level.